Fine Mapping of the Wheat Leaf Rust Resistance Gene Lr42 - Gill, Harsimardeep S. (Int J Mol Sci, 2019)
Leaf rust caused by Puccinia triticina Eriks is one of the most problematic diseases of wheat throughout the world. The gene Lr42 confers effective resistance against leaf rust at both seedling and adult plant stages. Previous studies had reported Lr42 to be both recessive and dominant in hexaploid wheat; however, in diploid Aegilops tauschii (TA2450), we found Lr42 to be dominant by studying segregation in two independent F(2) and their F(2:3) populations. We further fine-mapped Lr42 in hexaploid wheat using a KS93U50/Morocco F(5) recombinant inbred line (RIL) population to a 3.7 cM genetic interval flanked by markers TC387992 and WMC432. The 3.7 cM Lr42 region physically corresponds to a 3.16 Mb genomic region on chromosome 1DS based on the Chinese Spring reference genome (RefSeq v.1.1) and a 3.5 Mb genomic interval on chromosome 1 in the Ae. tauschii reference genome. This region includes nine nucleotide-binding domain leucine-rich repeat (NLR) genes in wheat and seven in Ae. tauschii, respectively, and these are the likely candidates for Lr42. Furthermore, we developed two kompetitive allele-specific polymorphism (KASP) markers (SNP113325 and TC387992) flanking Lr42 to facilitate marker-assisted selection for rust resistance in wheat breeding programs.